Differences in healthy longevity by HIV status and viral load among older South African adults: an observational cohort modelling study - Collin F. Payne, PhD; Brian Houle, PhD; Chido Chinogurei, MA; Carlos Riumallo Herl, PhD; Chodziwadziwa Whiteson Kabudula, PhD; Lindsay C. Kobayashi, PhD; Prof. Joshua A. Salomon, PhD; Jennifer Manne-Goehler, PhD (My University, 2022)
Background: The population of people living with HIV in South Africa is rapidly ageing due to increased survivorship attributable to antiretroviral therapy (ART). We sought to understand how the combined effects of HIV and ART have led to differences in healthy longevity by HIV status and viral suppression in this context. Methods: In this observational cohort modelling study we use longitudinal data from the 2015 baseline interview (from Nov 13, 2014, to Nov 30, 2015) and the 2018 longitudinal follow-up interview (from Oct 12, 2018, to Nov 7, 2019) of the population-based study Health and Ageing in Africa: a Longitudinal Study of an INDEPTH Community in South Africa (HAALSI) to estimate life expectancy and disability-free life expectancy (DFLE) of adults aged 40 years and older in rural South Africa. Respondents who consented to HIV testing, responded to survey questions on disability, and who were either interviewed in both surveys or who died between survey waves were included in the analysis. We estimate life expectancy and DFLE by HIV status and viral suppression (defined as <200 copies per mL) using Markov-based microsimulation. Findings: Among the 4322 eligible participants from the HAALSI study, we find a clear gradient in remaining life expectancy and DFLE based on HIV serostatus and viral suppression. At age 45 years, the life expectancy of a woman without HIV was 33·2 years (95% CI 32·0-35·0), compared with 31·6 years (29·2-34·1) a woman with virally suppressed HIV, and 26·4 years (23·1-29·1) for a woman with unsuppressed HIV; life expectancy for a 45 year old man without HIV was 27·2 years (25·8-29·1), compared with 24·1 years (20·9-27·2) for a man with virally suppressed HIV, and 17·4 years (15·0-20·3) for a man with unsuppressed HIV. Men and women with viral suppression could expect to live nearly as many years of DFLE as HIV-uninfected individuals at ages 45 years and 65 years. Interpretation: These results highlight the tremendous benefits of ART for population health in high-HIV-prevalence contexts and reinforce the need for continued work in making ART treatment accessible to ageing populations.